Explicit Evidence on an Implicit Contract - Andrew T. Young; Daniel Levy (Bar-Ilan University, Department of Economics, 2005)
We offer the first direct evidence of an implicit contract in a goods market. The evidence we offer comes from the market for Coca-Cola. We demonstrate that the Coca-Cola Company left a substantial amount of written evidence of its implicit contract with its consumers—a very explicit form of an implicit contract. In general, observing implicit contracts directly is difficult because of their implicit nature. In the case of Coca-Cola, however, we are able to document the Company not only saying that it had an important implicit contract with its consumers, but also acting on it. This study makes an additional and unique contribution by exploring quality as a margin of adjustment available to Coca-Cola. We present evidence that the implicit contract included a promise not only of a constant nominal price but also a constant quality. We document the dedication to a 6.5oz serving of the "Secret Formula." Indeed, during a period of over 70 years, we find evidence of only a single case of true quality change. By studying the margin of adjustment the Coca-Cola Company chose in response to changes in market conditions, we demonstrate that the perceived costs of breaking the implicit contract were large. In addition, we are able to offer one piece of direct evidence on the magnitude of these costs by studying the events surrounding the failed introduction of the New Coke in 1985.
Keywords: E12; E31; L14; L16; L66; M30; N80; A14; 330; Implicit Contract; Explicit Contract; Invisible Handshake; Customer Market; Long-Term Relationship; Price Rigidity; Coca-Cola; Nickel Coke